Catadores de sonhos : uma abordagem educativa sensível - Paim, Ilse Ana Piva (2010)
This paper investigates the series of paintings "Collectors of Dreams" and is part of the research in Educative Processes and Language. The problem of this research was: what does "Collectors of Dreams" series represent to Carazinho s community? Also, how the images promoted knowledge? Is it possible to sensitize the community through the images? Which Educational processes were triggered by the aesthetic paintings? Based on these questions, the general objective was to investigate the significance of the series "Collectors of Dreams" to Carazinho s community. One of the main authors which motivated the work was João-Francisco Duarte Júnior. Qualitative in nature, this study used the method auto-ethnographic (VERSIANI, 2005) and desk research (GIL, 1994). For reading images, employed the methodology of Ott (1997). Thus, it was categorization of information showing the importance of art as a territory of knowledge production, which allows sensitive education through images and promotes the aesthetic and environmental education. It is concluded that the series of ten works painted provided elements for an education geared to citizenship by recourse to an aesthetic of garbage, which in turn can cause sensitive education